The Widow Of The South - Hicks, Robert (New York Warner Books, 2005)
A story based on the true experiences of a Civil War heroine finds Carrie McGavock witnessing the bloodshed of the Battle of Franklin, falling in love with a wounded man, and dedicating her home as a burial site for fallen soldiers.
Include Illustrations, Maps and Bibliography
Keywords: American Civil War (1861-1865) -- Franklin, Battle of (Tennessee : 1864)